The potential of digital tools to promote sustainable production in the shrimp aquaculture sector: A case study of the Mekong Delta, Viet Nam - Giles, James; Kropff, Wietske; Grosjean, Godefroy; Quyen, Cao Le; Jallo, Courtney; Mayzelle, Megan (Deutsche Gesellschaft für Internationale Zusammenarbeit, 2021)
Viet Nam’s fishery sector plays a vital role in the economy. Together, aquaculture and capture fishing account for almost 5% of the national gross domestic product (GDP), and directly or indirectly provide income to 8.5 million people, or nearly 10% of the total population (FAO, 2019; Lebailly et al., 2017). Viet Nam’s vibrant aquaculture sector contributes approximately 65% of total fisheries exports and plays an important role in filling the gap between global seafood demand and the sustainable limits of capture fishing (Lebailly et al., 2017; Phung & Pham, 2018). The shrimp aquaculture sub-sector is a particularly critical pillar of the seafood industry; it represents the second largest share of national aquatic exports, making Viet Nam the third largest shrimp exporter globally (International Trade Centre (ITC), 1999; Phung & Pham, 2018). The brackish waters of Viet Nam’s Mekong Delta host the vast majority of the nation’s shrimp aquaculture, accounting for 84% of total production (GSO, 2020).